DEVELOPING ADOLESCENTS IN 21ST CENTURY: AN ISLAMIC AND WESTERN META-ETHNOGRAPHIC SYNERGY FOR MUSLIM PARENTS - Irfan Ullah (IJoLIS, 2024)
Introduction: The current study was the result of four major theory and practice-driven research gaps identified: firstly, „Pakistan Education Policy 2017‟s Islamic values and holistic development of child-related gap; secondly, Pakistan‟s latest Single National Curriculum, 2020‟s lack of connecting parenting and schooling gap; thirdly, Pakistan National Professional Standards for Teachers, 2009, standard 2 and standard 3 of 10 standards lacking up-to-date Islamic and Western blended parenting and teaching guidance gap, and fourthly, lack of any research based blended parenting or guidance program in concerned government departments. Aims: In this regard, the study explored Islamic and Western versions of adolescent developmental characteristics, principles, milestones, common challenges and their remedies.